2015
DOI: 10.1294/jes.26.129
|View full text |Cite
|
Sign up to set email alerts
|

A clinical case of equine fungal placentitis with reference to hormone profiles and ultrasonography

Abstract: Fungal placentitis is an infectious disease inducing abortion in pregnant mares. In the present report, we describe a field case of abortion caused by fungal placentitis with consecutive examinations. The progesterone level and combined thickness of the uterus and placenta (CTUP) were abnormal before the onset of clinical signs. Additionally, the estradiol level started to change before the appearance of clinical signs. Abnormal serum amyloid A values and an abnormal fetal heart rate were observed after the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In Thoroughbred, quarter, and American paint horses [ 13 , 14 , 20 ] and ponies [ 1 , 11 ] with placentitis, high CTUP values have been reported. In our study, all horses in the placentitis group (100%) showed CTUP values greater than those observed in the 75th percentile of the normal group, and the upper 25% of the normal group were included in this range.…”
Section: Discussionmentioning
confidence: 99%
“…In Thoroughbred, quarter, and American paint horses [ 13 , 14 , 20 ] and ponies [ 1 , 11 ] with placentitis, high CTUP values have been reported. In our study, all horses in the placentitis group (100%) showed CTUP values greater than those observed in the 75th percentile of the normal group, and the upper 25% of the normal group were included in this range.…”
Section: Discussionmentioning
confidence: 99%
“…Although the synergistic action of progesterone and estrogen is generally essential for mares, as in most mammals, for maintaining successful pregnancy, estrogen plays a dominant role in the maintenance of uterine elongation when the fetus grows rapidly in late pregnancy [9,10,11,12]. Therefore, monitoring circulating estradiol and progesterone is useful for detecting clinical signs of abortion, stillbirth, and perinatal fetal death during late pregnancy in mares [19,20,21,22]. …”
mentioning
confidence: 99%